Molecular analysis of low‐level mosaicism of the IKBKG mutation using the X Chromosome Inactivation pattern in Incontinentia Pigmenti. Issue 12 (21st October 2020) - Kawai, Miki; Kato, Takema; Tsutsumi, Makiko; Shinkai, Yasuko; Inagaki, Hidehito; Kurahashi, Hiroki
Abstract: Background: Incontinentia pigmenti (IP) is a rare X‐linked disorder affecting the skin and other ectodermal tissues that is caused by mutation of the IKBKG / NEMO gene. Previous studies have reported that the overall mutation detection rate in IP is ~75%. We hypothesized that a low‐level mosaicism existed in the remaining cases. Methods: Genomic variations in the IKBKG gene were examined in 30 IP probands and their family members. Standard mutational analyses were performed to detect common deletions, nucleotide alterations, and copy number variations. To assess skewing of the X chromosome inactivation (XCI) pattern, a HUMARA assay was performed. We compared the results of this analysis with phenotype severity. Results: Pathogenic variants were identified in 20 probands (66.7%), the rate of detection was suboptimal. The remaining 10 probands tended to manifest a mild phenotype with no skewed X chromosome inactivation that is generally observed in IP patients. Quantitative nested PCR and digital droplet PCR were performed for the 10 patients and mosaicism of the common IKBKG deletion were identified in five patients. Conclusion: Overall, we detected 25 IKBKG mutations (83.3%). Determination of the XCI value in advance of mutational analyses for IP could improve the mutation detection rate. Our improved detection rate for these mutations, particularly those with a low‐level mosaicism, may present opportunities for appropriate genetic counseling. Abstract : In our study, genomic variations in the IKBKG gene were examined in 30 IP probands and their family members. Standard mutational analyses identified pathogenic variants in 20 probands. The remaining 10 probands tended to manifest a mild phenotype with no skewed X chromosome inactivation. Quantitative nested PCR and digital droplet PCR identified an additional five patients with mosaicism of the common IKBKG deletion. Overall, we detected 25 IKBKG mutations.